The use of interactional metadiscourse in the construction of gender identities among Malaysian ESL learners - Roslina Abdul Aziz; Chin, Chiu Jin; Noli Maisarah Nordin (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2016)
The study investigates how interactional metadiscourse resources are used to articulate and construct gender identity among ESL learners in Malaysia. The main purpose of the study is to provide language practitioners with empirical data of how gender is projected in the academic writings of ESL learners and to what extent learners’ writings are affected by their gender. The data can then be utilised for the design and development of more effective academic writing courses in Malaysia. Quantitative and qualitative analyses were performed on the similarities and differences in the use of interactional metadiscourse resources, namely; hedges, boosters, attitude markers, engagement markers and self mentions between male and female ESL learners involved in the study. The findings of the quantitative analyses show no obvious differences in the writing style of female and male writers in the study, while the qualitative findings reveal slight differences in the way writers position themselves in the reader/writer interaction and in the expression of agreement statement.